The attitude of preventing opportunistic infections among PLHIV/AIDS attending non-governmental organization (Kuldesak) Depok City, Indonesia - Talitha El Zhafira Hadi; Helda Helda (Malahayati International Journal of Nursing and Health Science, 2023)
Background: The number of people living with HIV and AIDS (PLWHA) is increasing and it has become a pandemic in various parts of the world. However, there are still limited AIDS countermeasures in preventing death, one of which is by reducing opportunistic infections.Purpose: To determine the factors associated with the attitude of preventing opportunistic infections among PLHIV/AIDS attending non-governmental organization (Kuldesak) Depok City, IndonesiaMethod: An analytic research with a cross-sectional research design which aims to determine the relationship between the independent variables and the dependent variable. The number of samples in this study were 71 PLHIV attending non-governmental organization “Kumpulan Dengan Segala Aksi Kemanusiaan” (Kuldesak) Peer Support Group (PSG)  Depok City, Indonesia. Samples were taken using a non-random sampling technique with purposive sampling.Results: Obtained that three variables influenced the attitudes to prevent opportunistic infection in PLWHA, namely perceived susceptibility (AOR = 4,98; 95% CI = 1,459-17,029), perceived severity (AOR = 4,04; 95% CI = 1,161-14,079) and perceived benefit (AOR = 7,13; 95% CI = 1,846-27,601).Conclusion: Almost half of all respondents in the Kuldesak Peer Support Group (PSG) Depok City have a low attitudes to prevent opportunistic infection. Perceived benefit was the most dominant predictor in determining attitudes to prevent opportunistic infection.Suggestion: In order to further develop this research and provide education so that the attitude of OI preventing, especially in PLWHA, is better than before.